Government of Rajasthan Draft Annual Plan 1994-95 Planning Department - Planning Commission (Planning Commission, 1994)
The area West of Aravallis is characterised by extremes of temperature, long period of severe drought, accompanied by high winds and low to semi arid conditions of humidity. The climate of the State in general is characterised as driest in the country and having large variations in maximum day temperature and minimum night temperature. The rain fall in the State is not only meagre but it also varies rather significantly from year to year arid that creates drought conditions quite frequently. Among all the States in the country, Rajasthan with its meagre water resources and perilous dependence on scanty, low and uncertain rain fall is most vulnerable to drought conditions. Rajasthan has about 1 per cent water resources of the country. In nearly 2/3rd of the area, either the water is available at a great depth or at long distance and in many areas it is unfit for human consumption. In terms of providing drinking water the situation is also an endemic and deteriorating one.
Draft Annual Plan 1994-95
Government of Rajasthan